Increased expression of forkhead box protein 3 gene of regulatory T cells in patients with active tuberculosis - Beiranvand, Elham; Abediankenari, Saeid; Rezaei, Mohammad Sadegh; Khani, Soghra; Sardari, Soroush; Beiranvand, Behnoush (Inflammation & allergy drug targets, 2014)
Cell mediated immunity is the most important response against Mycobacterium tuberculosis (MTB). Regulatory T cells (Treg) play a vital role in suppressing the effector T cell response in tuberculosis (TB) patients. Forkhead box protein 3 (Foxp3) is an important regulator of Treg cells development and function. In this study, we showed that the expression of Foxp3 gene in Treg cells is increased in patients with active tuberculosis. In a case-control study, 183 TB patients and 183 controls were recruited according to ethnicity, gender and living area. Then, after isolation of peripheral blood mononuclear cells (PBMCs), FoxP3 gene expression was studied by real-time PCR. The expression of this gene in patients with pulmonary and extra-pulmonary tuberculosis was 2.8 fold higher than normal subjects (CI=1.29±2.37, P≤0.001). Also comparing the patients with pulmonary tuberculosis and the control group, a significant difference was observed (CI=1.81±2.96, P≤0.001). FoxP3 gene expression was 1.5 fold higher in women with pulmonary and extrapulmonary tuberculosis than in men with tuberculosis (CI=0.12±2.01, P=0.02). According to this study, the increased Foxp3 gene expression in patients with TB was observed and this may play as a contributing factor to suppression of Th1-type immune responses.